Electrical Activity of the Mouse Pulmonary Vein Myocardium - Yayoi Tsuneoka; Yuka Kobayashi; Yoriko Honda; Iyuki Namekata; Hikaru Tanaka (Elsevier, 2012)
We recorded the electrical activity from the myocardial layer of isolated mouse pulmonary veins with the glass microelectrode technique. Spontaneous electrical activity was observed in about half of the preparations, which appeared either as constant firing or as repetitive bursts. Noradrenaline enhanced, while acetylcholine reduced, automatic activity. The action potentials evoked in quiescent preparations showed a resting membrane potential less negative than the atria and an extremely rapid early repolarization followed by a late plateau. The present study revealed that the mouse pulmonary vein myocardium shows diverse electrical activity, which is influenced by autonomic neurotransmitters. Keywords:: pulmonary vein myocardium, automaticity, autonomic neurotransmitter